Effects of injection timing and rail pressure on particulate size-number distribution of a common rail DI engine fueled with fischer-tropsch diesel synthesized from coal. (April 2021) - Geng, Limin; Xiao, Yonggang; Li, Shijie; Chen, Hao; Chen, Xubo
Abstract: The use of coal-based F-T diesel in automobiles can alleviate the shortage of petroleum and promote clean utilization of coal. In this study, the effects of injection timing and rail pressure on the emissions of NO x, soot, and UFPs from F-T diesel and petro-diesel were investigated in a common rail DI engine under a constant speed and various loads. The rail pressures are selected as 70 MPa and 100 MPa, whereas the injection timings are regulated at 2 °CA, 6 °CA, 10 °CA, 14 °CA, and 18 °CA BTDC. Experimental results indicate that advancing the injection timing or increasing the rail pressure shall result in higher NO x and lower soot emissions. When the fuel injection timing was advanced from 2 °CA to 18 °CA BTDC, the number concentration of UFPs first decreased and then increased at low loads, whereas the number concentration of UFPs always decreased at medium and high loads, the peak number concentration transferred from the size range of accumulation mode particles to that of nucleation mode particles, and the geometric mean diameters of UFPs emitted by the F-T diesel and petro-diesel reduced by an average of 23.4% and 26.19% under different test conditions, respectively. In addition, when the rail pressure was increased from 70 MPa to 100 MPa, the number concentration of UFPs of F-T diesel and petro-diesel decreased by 39.78% and 53.75%, and their geometric mean diameters of UFPs decreased by 14.09% and 12.5%, respectively. Compared to petro-diesel, F-T diesel has a lower number concentration of UFPs, smaller geometric mean diameter of UFPs, and a higher ratio of nucleation mode particles. With regard to the lowest number concentration of UFPs, when coal-based F-T diesel is used, the injection timing of the original engine can be advanced by 4–8 °CA at low loads. Highlights: Increasing rail pressure and advancing injection timing lead to an increase in NOx emission and a decrease in soot. At low loads, the number concentration of UFPs first decreases and then increases with advancing injection timing. The size distribution of UFPs becomes smaller with advancing injection timing. Increasing the rail pressure results in a lower number concentration of UFPs and a higher ratio of NMPs. Compared to petro-diesel, the number concentration and the GMDs of UFPs from F-T diesel are smaller.